2017
DOI: 10.1039/c6tb02524b
|View full text |Cite
|
Sign up to set email alerts
|

Targetable and fixable rotor for quantifying mitochondrial viscosity of living cells by fluorescence lifetime imaging

Abstract: A fixable probe, named Vis-A, to quantify mitochondrial viscosity of living cells by fluorescence lifetime imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…It is important to monitor the mitochondrial membrane potential. Carbonyl cyanide 3‐chlorophenylhydrazone (CCCP) can induce the decrease of the mitochondria membrane potential rapidly 30–33. Thus, the response of the MMP‐CDs toward the CCCP induced mitochondrial membrane potential decrease was then examined.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to monitor the mitochondrial membrane potential. Carbonyl cyanide 3‐chlorophenylhydrazone (CCCP) can induce the decrease of the mitochondria membrane potential rapidly 30–33. Thus, the response of the MMP‐CDs toward the CCCP induced mitochondrial membrane potential decrease was then examined.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial matrix diffusion has been studied with steady-state anisotropy [21], fluorescence correlation spectroscopy (FCS) [4] and fluorescence recovery after photobleaching (FRAP) [22], and has been linked to complex I deficiency and Leigh’s syndrome. Furthermore, a few matrix-targeting lifetime FMRs have been reported [16],[23],[24]. Changes in mitochondrial membrane fluidity have been studied with steady-state anisotropy and linked to a range of neurodegenerative diseases and ageing [2],[3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated the usefulness of complementary techniques for measuring viscosity of discrete subcellular locations in living cells. Whilst numerous previous attempts to target molecular rotors in living cells have relied on exploiting the unique properties of given organelles 7,8 , our work represents one of the first attempts at producing a generic mechanism to target BODIPY to any selected organelle or structure. We measured the relative viscosities of a host of organelles, as well as showcasing the BG-BODIPY's prospects for measuring absolute viscosity in both membrane-bound and membraneless organelles.…”
Section: Discussionmentioning
confidence: 99%
“…Levitt et al (2009) 6 used two meso-substituted BODIPY based fluors conjugated to hydrophobic groups designed to drive indiscriminate incorporation into the hydrophobic interior of non-aqueous cellular membranes, and discovered that the intracellular environment contains a wide range of viscosities. Several groups have targeted boron-dipyrrin (BODIPY) modified by the addition of triphenylphosphonium to target the dye to the mitochondria with varying degrees of success 7,8 . More recently, Chambers et al (2018) 9 , have developed a chloroalkane -BODIPY capable of targeting to specific organelles via a transiently expressed HALO-tag protein targeted to mitochondria or the ER lumen.…”
Section: Introductionmentioning
confidence: 99%